Value stream mapping and simulation in a construction company - Tam, Yeen Shin, 1991-, author; Wong, Kuan Yew, supervisor; Fakulti Kejuruteraan Mekanikal (2015)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Industri)) - Universiti Teknologi Malaysia, 2015